MENINGKATKAN HASIL BELAJAR SHOOTING DALAM SEPAKBOLA MELALUI PENDEKATAN PERMAINAN BOLA INOVATIF - Teguh Heriyanto; Andry Akhiruyanto (Universitas Negeri Semarang, 2015)
This research was conducted at the District 02 Elementary School Bojong Bojong Tegal with class IV study subjects by the number of 30 students consisting of 18 boys and 12 student daughter. This study uses 2 cycles, where each cycle consists of: 1) planning, 2) implementation of action 3) observation; 4) reflection. This research is a learning object shooting by using innovative ball game. Data collection techniques were used that documentation, observation sheet (observation), written and practical test, completeness assessment of learning outcomes through the use of data analysis techniques percentage description. This research method is Classroom Action Research.The results showed that the application of innovative methods of ball games can improve learning outcomes shooting football in the fourth grade students of SD Negeri 02 Bojong District of Tegal Bojong Year 2014 From the results of the analysis are improving student learning outcomes from the first cycle to the second cycle.